Analysis of the system for control of physical fitness of army military servants of RUSSIA, THE USA AND VENEZUELA - Salmeron Mallorca David Alejandro,; Ponomarev V.V. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to conduct a theoretical analysis of the system for monitoring the physical fitness of military personnel of various armies of the world, systematize their content, identify general trends and directions of physical training of military personnel in world practice. Methods and structure of the study. The relevant scientific and methodological literature was analyzed on the topic of the study. The basis was an analysis of the physical fitness monitoring system of the two best armies in the World: Russia and the USA, as well as the Armed Forces of Venezuela. Results and conclusions. It is necessary to improve the content of physical training of military personnel of the armies of Russia, the USA and Venezuela, namely: to include complex control exercises to simultaneously assess all basic physical qualities, pay attention to the development of mobility of the musculoskeletal system of military personnel, expand the content of physical training based on the inclusion of modern technologies and means taking into account the changing tactics and strategies of military conflicts in the modern World.